Student attendance system using barcode scanner - Nur Zalfarina, Azmee (2014)
Student attendance system play significant role in order to justify academic outcome of a student in class overall. Unfortunately, there is no automated attendance record keeping application available nowadays. Through interview session, Student Attendance System development team, have identified that lecturers and faculty management face problems in recording and managing attendance of their students. The existing manual student attendance system is inefficient and not systematic. The existing manual student attendance system needs students to take time to sign the attendance sheet during class. It also affecting the efficiency of lecturers where lecturers have to calculate the students' attendance percentage throughout the semester and come out with their own, not standardize students' attendance report. The purpose of this project is to gather students' attendance by using students' matric card. Therefore, Student Attendance System Using Barcode Scanner has been proposed and developed. Need for a tool to systematically keep the students attendance record increased due to increasing number of students every year. Upon completion of Student Attendance System Using Barcode Scanner, user acceptance testing conducted among potential end users.